PENGARUH PEMBERIAN PUPUK KANDANG SAPI DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L) Merill): Kedelai, pupuk kandang sapi, pupuk fosfor - erviana, nurma; Bahri, Saiful; Sumarmi, Sumarmi (innofarm, 2023)
Research tittle "The effect of dosing of cow manure and phosphorus fertilizer on the growth and yield of soybean (Glycine max (L.) Merril)" plants. This study aims to determine the effect of the use of cow manure and phosphorus fertilizers as well as the right dosage on the growth and yield of soybean (Glycine max (L.) Merrill). The research was conducted at the Tohudan Horticultural Seed Garden, Colomadu District, Karanganyar Regency from 10 October 2022 to 16 February 2023. The experimental design used a Regression Polynomial Split Plot Design consisting of 2 factors with 3 repetitions. The first factor Cow manure (K) consisted of 4 levels, namely: Without fertilizer 0 kg/plot (K0), 2.56 kg/plot (K1), 3.86 kg/plot (K2), 5.12 kg/plot (K3) and the second factor of phosphorus (P) fertilizer which consists of 4 levels namely: without phosphorus 0 g/plant (P0), 1.2 g/plant (P1), 2.4 g/plant (P2), 3, 6 g/plant (P3). The results showed that the dose of cow manure 5.12 kg/plot and phosphorus fertilizer dose of 3.6 g/plot gave the highest results in the observation of plant height 105.55 (cm), number of leaves 97.75 (strands), number of flowers 27 .92 (stalk). The dose of cow manure 5.12 kg/plot and phosphorus fertilizer dose of 3.6 g/plot gave the highest yield on the number of full pods 172.34 (fruits), the number of seeds 189.24 grains, the weight of wet pods 526.42 (g), the weight of dry seeds per plot was 172.48 (g), the weight of 100 seeds was 24.56 (g).